A review on microfiltration membranes: fabrication, physical morphology, and fouling characterization techniques - Alsoy Altinkaya, Sacide (Frontiers in Membrane Science and Technology, 2024)
Microfiltration is a commonly used pressure-driven membrane separation process for various applications. Depending on the manufacturing method, either tortuous or capillary pore structures are obtained. The structure plays an important role in controlling flux, selectivity, but most importantly, the fouling tendency of the membrane. This review attempts to cover past and current developments in physical morphology and fouling characterization methods, along with the manufacturing methods for microfiltration membranes. The limitations and advantages of direct microscopic techniques and gas-liquid displacement as an indirect method are discussed for physical characterization. Additionally, the current state of the art and technical challenges for various in-situ and ex-situ fouling characterization techniques are also discussed. Finally, some directions for future research are outlined.